FACTORS ASSOCIATED WITH INCOMPLETE CONSTRUCTION OF PIT LATRINES AND THEIR PUBLIC HEALTH RISK IN KARONGI DISTRICT RURAL HOUSEHOLDS, RWANDA. - Vincent Tuyishime, Dr. Alphonse Habineza, Ephigenie Kayirangwa, Raphael Ndahimana (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Background Globally, 2 billion people lack access to improved latrines, with 60% of these individuals residing in rural areas of Asia and Africa. In Sub-Saharan Africa, 41% of the population continues to use unimproved latrines, and in Rwanda, 25% of the population still relied on unimproved latrines in 2020, with most using pit latrines presenting significant structural deficiencies. Despite being a primary sanitation facility in developing countries, many pit latrines lack essential structural and design qualities. There is limited understanding of the factors influencing poor pit latrine constructions and the associated health risks. This study aims to assess the factors related to incomplete construction of pit latrines and their public health risks in Karongi district rural households in Rwanda, contributing to efforts to improve sanitation facilities in similar settings. Methods A cross-sectional study design was carried out on 288 households, were sampled from 30,900 rural households using fisher formula. A cluster sampling technique was used to select participants for the study. Data were collected using pre-tested interview-administered questionnaire and observation technique. Data were analyzed and presented using SPSS version 22. Multivariable logistic regression analysis was performed to identify variables associated with incomplete construction levels of pit latrine and their public health risk in rural Karongi district, Rwanda Results The study revealed that among 288 households, 73.6% had pit latrines at the superstructure level, while 26.4% had them at the sub-superstructure level. Several significant factors were associated with incomplete construction levels of pit latrines. Households expressing concern about latrine security (in terms of collapse) had higher odds of incomplete construction levels (OR: 3.7, 95% CI: 1.56-8.95). Similarly, households expressing neutrality about latrine security also had higher odds of incomplete construction levels (OR: 2.9, 95% CI: 1.07-7.90). Additionally, households perceiving their latrine privacy status as poor were significantly more likely to have incomplete construction levels (OR: 4.9, 95% CI: 1.44-6.99). Furthermore, the practice of digging new pits to manage filled ones was identified as a significant health risk associated with incomplete construction levels (OR: 4.0, 95% CI: 1.77-9.20) in Karongi district rural households. Conclusion This study emphasizes the critical need to address incomplete construction levels of pit latrines despite population is found risk-aware, and guide mitigation strategies to reduce environmental health risks in Karongi rural households and similar communities. It underscores the importance of increasing community knowledge about the various incomplete construction levels of pit latrines and their associated public health risks. The study recommends that Karongi district authorities leverage sanitation awareness initiatives, particularly by educating the community about risk awareness, integrating related subjects into community norms, economic strengthening and promoting attitudes that encourage individual families to adopt fully constructed pit latrines.